Living theodrama : reimagining theological ethics - Vander Lugt, Wesley, 1981- (Ashgate studies in theology, imagination, and the arts., 2014)
Offering an imaginative approach through dialogue with theatrical theory and practice, Vander Lugt demonstrates a new way to integrate actor-oriented and action-oriented approaches to Christian ethics within a comprehensive theodramatic model. This book contains not only a fruitful exchange between theological ethics and theatre, but it also presents a promising method for interdisciplinary dialogue between theology and the arts that will be valuable for students and practitioners across many different fields.